2018
DOI: 10.5513/jcea01/19.3.2062
|View full text |Cite
|
Sign up to set email alerts
|

Application of multi-criteria decision making for the selection of apple varieties for the Northwestern region of B&H

Abstract: The selection of the appropriate apple varieties is one of the most important decisions in orchards establishing. The paper gives the methodology for estimating the most suitable varieties of apples when establishing orchards according to modern market demands. This methodology is based on the DEX method for hierarchybased multi-criteria decision making. The model developed in this paper was applied on four apple varieties, whereby an expert evaluation was used. The experts included in evaluation are from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Based on that, it can be concluded that, based on expert opinion, economic criteria have a more significant role in raising pear orchards than technological criteria. However, in this research, all criteria were taken into account in order for the decision to be complete [10], and all of them were given greater importance in certain scenarios in sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on that, it can be concluded that, based on expert opinion, economic criteria have a more significant role in raising pear orchards than technological criteria. However, in this research, all criteria were taken into account in order for the decision to be complete [10], and all of them were given greater importance in certain scenarios in sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lučić, et al [9], the choice of variety depends primarily on their purpose for consumers, and what can be produced from these varieties. In addition, when choosing a fruit variety, it is necessary to consider all aspects and make a decision in such a way as to choose the variety that best meets the set investment objectives [10]. On that occasion, it is necessary to synthesize various collected data, as well as to consider all aspects of future investment.…”
Section: Introductionmentioning
confidence: 99%
“…Draginčić et al [22] used the Simple Additive Weighting (SAW) method, the AHP and Cardinal consensus model using the Group multi-criteria decision making (GMCDM) when selecting a grape variety. Rozman et al [23] used the DEX method to select the plum variety that gives the best results in integrated fruit production Maksimović et al [24] used the DEX method to select the apple variety that gives the best results in North-western Bosnia and Herzegovina. Also, Maksimović et al [25] used the DEX method to select the fruit species that give the best results in integral fruit production.…”
Section: Literature Reviewmentioning
confidence: 99%